Talkin' 'bout a revolution? From quiescence to resistance in the contemporary university. Issue 4 (September 2020) - Bowes-Catton, Helen; Brewis, Jo; Clarke, Caroline; Drake, Deborah H; Gilmour, Alison; Penn, Alison
In discussing the events leading up to the resignation of the former Open University Vice Chancellor in April 2018, we focus on the enactment of a form of resistance against proposals for the university through a WhatsApp group, enabling rapid information exchange, discussion of tactics and concrete planning for action. We suggest our group – 'the Hive' – was unusual because, first, it countered the politically quiescent trend in academia to comply (at least outwardly) with neoliberalisation, and/or only to write about it, as opposed to mounting challenges. Second, the Hive was virtual, comprising various staff categories, including people based off-campus; it operated almost entirely online and many members had never met face-to-face. This for us evokes notions of the multitude. Third, the group exemplifies alternative forms of solidarity and resistance in other ways, being non-hierarchical, highly pluralist and non-exclusionary. Finally, our Hive provided a supportive, caring space for resisters, which we suggest emerged partly through members' love for the distinctive social mission of The Open University – although our story also provides hope for harnessing similar emotions within other academic institutions.